PENINGKATAN EKONOMI MASYARAKAT BERBASIS KELUARGA MELALUI BUDIDAYA HORTIKULTURA DI KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - Komul, Yulianus Dominggus; Selanno, Frenly Marvi; Tita, Frank Samelino (Universitas Pattimura, 2023)
Agricultural business has an important role for the national economy. In 2020, the Central Statistics Agency (BPS) released the agricultural sector's GDP as the highest contributor to national economic growth in the second quarter of 2020, which decreased by 4.19% and year on year (yoy) decreased by 5.32%. . Agricultural GDP grew by 16.24% in the second quarter of 2020, which means that the agricultural sector still contributes 2.19% to national economic growth (Dirjen Horticulture: 2021). In an effort to increase the production of various agricultural commodities in Wanasa Hamlet, Tehoru District, Central Maluku Regency, there are still quite large opportunities for the family sector. The main purpose of this volunteer activity is to provide new understanding and knowledge as well as to carry out direct practice of horticultural crop cultivation techniques and patterns that were originally known by the community conventionally but are more academically improved to the people who make up most of their livelihoods. as a farmer and hunter, to utilize vacant land and yards by cultivating Horticultural crops with the aim of meeting household consumption needs and also providing additional income for the family. Community service activities are carried out in Wanasa Village which is located in Tehoru District, Central Maluku Regency and takes place on October 15-17 2021.